Contaminant-degrading bacteria are super carriers of antibiotic resistance genes in municipal landfills: A metagenomics-based study - Fang-Zhou Gao; Wei-Li Jia; Bing Li; Min Zhang; Liang-Ying He; Hong Bai; You-Sheng Liu; Guang-Guo Ying (Environment International)
Municipal landfills are hotspot sources of antimicrobial resistance (AMR) and are also important habitats of contaminant-degrading bacteria. However, high diversity of antibiotic resistance genes (ARGs) in landfills hinders assessing AMR risks in the affected environment. More concerned, whether there is co-selection or enrichment of antibiotic-resistant bacteria and contaminant-degrading bacteria in these extremely polluted environments is far less understood. Here, we collected metagenomic datasets of 32 raw leachate and 45 solid waste samples in 22 municipal landfills of China. The antibiotic resistome, antibiotic-resistant bacteria and contaminant-degrading bacteria were explored, and were then compared with other environmental types. Results showed that the antibiotic resistome in landfills contained 1,403 ARG subtypes, with the total abundance over the levels in natural environments and reaching the levels in human feces and sewage. Therein, 49 subtypes were listed as top priority ARGs for future surveillance based on the criteria of enrichment in landfills, mobilizable and present in pathogens. By comparing to those in less contaminated river environments, we elucidated an enrichment of antibiotic-resistant bacteria with contaminant-degrading potentials in landfills. Bacteria in Pseudomonadaceae, Moraxellaceae, Xanthomonadaceae and Enterobacteriaceae deserved the most concerns since 72.2 % of ARG hosts were classified to them. Klebsiella pneumoniae, Acinetobacter nosocomialis and Escherichia coli were abundant multidrug-resistant pathogenic species in raw leachate (∼10.2 % of total microbiomes), but they rarely carried contaminant-degradation genes. Notably, several bacterial genera belonging to Pseudomonadaceae had the most antibiotic-resistant, pathogenic, and contaminant-degrading potentials than other bacteria. Overall, the findings highlight environmental selection for contaminant-degrading antibiotic-resistant pathogens, and provide significant insights into AMR risks in municipal landfills.